Enhancing English Vocabulary Acquisition in Reading Instruction Through Multiple Intelligences Approach - Miolo, Sartin; Pilongo, Jolanda Hulda Deborah; Sambouw, Elsje L; Luwiti, Sri Rumiyati Ningsih (TRANSBAHASA, 2023)
This research explores innovative strategies to improve students' vocabulary mastery in English language teaching. Utilizing cognitive skill-based approaches, such as the